HUBUNGAN IKLIM ORGANISASI DENGAN SEMANGAT KERJA GURU DI SMK NEGERI I KECAMATAN AMPEK ANGKEK KABUPATEN AGAM - SRI RAHAYU (Jurnal Bahana Manajemen Pendidikan, 2016)
The phenomenon of the decline in the morale of teachers, it can be seen from teachers who do not do their job well, teachers who only teach but function less educated. The purpose of this study was to determine the relationship of climate organizations of the morale of teachersat SMK1 Agam District of Ampek Angkek.This study is correlational, which describesthe relationshipof organizational climate with the morale of teachers. The study population was all teachers in SMK1 Agam District of Ampek Angkek totaling 75 people. The sample size is determined by krejcie table which is 5% ofthe population is determined so that the number of samples obtained in the amount of63 people. Sampling using proportionate stratified random sampling. There search instrumentis a  Likert scale questionnaire that has beentested Validity and Reliability. Data were analyzed using product moment correlation formula.